GLOBALIZATION AND STOCK MARKET GROWTH IN NIGERIA - Foluso Ololade Oluwole (European Scientific Journal, ESJ, 2014)
The subject of the interrelationship that exists between globalization and stock market growth has been an issue of both theoretical and empirical investigations. The a priori expectation is that globalization will impact positively on stock market growth in Nigeria. This work therefore, attempts to find out if there is any impact globalization has on stock market growth in Nigeria. Data for this work were obtained mainly from secondary sources and analysed with the use of ordinary least square simple regression model. The study shows that globalization through trade liberalization and financial integration had a significant impact on the growth of Nigerian stock market. Also, the study equally shows that globalization promotes regional and global integration of Nigerian stock market. However, the study did not overlook the volatility inherent in globalization.